Predictive value of PD-L1 expression in response to immune checkpoint inhibitors for esophageal cancer treatment: A systematic review and meta-analysis - Noori, Maryam; Yousefi, Amir-Mohammad; Zali, Mohammad Reza; Bashash, Davood (Frontiers in Oncology, 2022)
Background: Programmed death-ligand-1 (PD-L1) molecule is a well-known predictive biomarker for the efficacy of immune checkpoint inhibitors (ICIs) in several cancers. Present systematic review and meta-analysis aimed at investigating the role of PD-L1 in predicting the effectiveness of programmed death-1 (PD-1)/PD-L1 inhibitors in patients suffering from esophageal cancer. Methods: We searched PubMed, Scopus, Web of Science, and EMBASE databases as of March 25, 2022 for retrieving the potential relevant randomized controlled trials (RCTs). The pooled hazard ratios (HR) and the corresponding 95% confidence intervals (95%CIs) were calculated for the outcomes of overall survival (OS) and progression-free survival (PFS) in patients with esophageal tumor expressing different values of PD-L1 based on combined-positive score (CPS) and tumor proportion score (TPS). Results: Eleven studies with a total of 5,418 participants were included. While there were no difference in the OS of CPS<1 patients in the intervention with control group, patients bearing esophageal tumors with a CPS≥1 (HR 0.65, 0.56-0.74) treating by ICIs showed a significant improvement in OS relative to the control agents. Accordingly, patients with CPS<5 (HR 0.75, 0.58-0.98), CPS≥5 (HR 0.64, 0.53-0.77), CPS<10 (HR 0.86, 0.76-0.98), and CPS≥10 (HR 0.65, 0.56-0.75) had improved OS; however, a significant longer OS was observed in cases who expressed higher values of CPS=10 (p=0.018). In terms of TPS, a significant greater benefit in prolonging the OS came from TPS≥1% PD-L1 expressing tumors in comparison to TPS<1% tumors, suggesting this cut-off as another predictor of PD-1/PD-L1 inhibitors efficacy. Notably, in the subgroup analysis when the cut-off value of CPS=10 or TPS=1% was selected, Nivolumab was the best ICI that improved survival of PD-L1 positive patients. In patients with negative PD-L1 expression, Toripalimib is the only ICI which could prolong the OS of patients with the cut-off value of CPS=10. Conclusion: Among patients suffering from esophageal cancer, PD-L1 CPS=10 and TPS=1% expression thresholds seems to be predictive for lower rate of mortality when PD-1/PD-L1 inhibitors are administrated; however, further large-scale trials are required for confirming the findings of present study.